TRIM8 regulates stemness in glioblastoma through PIAS3‐STAT3. Issue 3 (15th February 2017) - Zhang, Changming; Mukherjee, Subhas; Tucker‐Burden, Carol; Ross, James L.; Chau, Monica J.; Kong, Jun; Brat, Daniel J.
Abstract : Glioblastoma (GBM) is the most malignant form of primary brain tumor, and GBM stem‐like cells (GSCs) contribute to the rapid growth, therapeutic resistance, and clinical recurrence of these fatal tumors. STAT3 signaling supports the maintenance and proliferation of GSCs, yet regulatory mechanisms are not completely understood. Here, we report that tri‐partite motif‐containing protein 8 (TRIM8) activates STAT3 signaling to maintain stemness and self‐renewing capabilities of GSCs. TRIM8 (also known as 'glioblastoma‐expressed ring finger protein') is expressed equally in GBM and normal brain tissues, despite its hemizygous deletion in the large majority of GBMs, and its expression is highly correlated with stem cell markers. Experimental knockdown of TRIM8 reduced GSC self‐renewal and expression of SOX2, NESTIN, and p‐STAT3, and promoted glial differentiation. Overexpression of TRIM8 led to higher expression of p‐STAT3, c‐MYC, SOX2, NESTIN, and CD133, and enhanced GSC self‐renewal. We found that TRIM8 activates STAT3 by suppressing the expression of PIAS3, an inhibitor of STAT3, most likely through E3‐mediated ubiquitination and proteasomal degradation. Interestingly, we also found that STAT3 activation upregulates TRIM8, providing a mechanism for normalized TRIM8 expression in the setting of hemizygous gene deletion. These data demonstrate that bidirectional TRIM8‐STAT3 signaling regulates stemness in GSC. Abstract : Glioblastoma (GBM) stem‐like cells contribute to the rapid growth, therapeutic resistance, and clinical recurrence of this high grade primary brain tumor. We have shown that TRIM8 activates STAT3 signaling to maintain stemness and self‐renewing capabilities in GBM stem‐like cells by suppressing PIAS3, an inhibitor of STAT3. A bidirectional positive regulatory loop exists involving TRIM8, PIAS3, and STAT3.